Characteristics of Morphological Changes in Fins according to Larval Growth of Red Spotted Grouper, Epinephelus akaara - Jung, Hee-Kyung; Lee, Chi-Hoon; Lee, Young-Don (Balsaeng'gwa saengsig, 2024)
This study investigated the fin development and morphological characteristics according to larval growth in order to obtain information on behavioral characteristics and optimal stocking density during red seed grouper seed production. To examine the growth and fin development process of the larvae, we randomly sampled at 1, 3, 5, 7, 9, 10, 11, 13, 15, 17, 19, 20, 25, 30, 39, 45, 51, and 72 days after hatching. External morphology was observed and measured using an optical microscope. To observe skeletal development, larvae at 13, 20, 30, and 72 days after hatching were fixed in formalin and stained for cartilage and bone examination. At 9-10 DAH, red spotted grouper larvae (2.74±0.1 to 3.0±0.2 mm TL) exhibited a second dorsal fin spine and pelvic fin spine, which subsequently elongated. At 19-20 DAH, the larvae (5.7±0.1 to 6.1±0.1 mm TL) have the lengths of the second dorsal fin spine and pelvic fin spine average 34% and 31% to total length, respectively. From 30 to 72 DAH (12.6±0.4 to 56.0±0.2 mm TL), the length of the second dorsal fin spine and pelvic fin spine to total length decreased from 27% to 8% for the dorsal fin and 21% to 14% for the pelvic fin, respectively. At 30 DAH (12.6±0.4 mm TL), the larvae reached the complete count of fin rays in each fin. At 39 DAH (20.28±3.07 mm TL), the larvae had fin shapes similar to those of adults. At 13-30 DAH (4.2±0.1 to 12.6±0.9 mm TL), barbs and spinules were distributed along the ridges of the second dorsal and pelvic fin spines. However, at 72 DAH, these barbs and spinules were no longer observed on the fins. During the seed production process, red spotted grouper larvae tend to cluster in the morning, and during this time, entanglement of barbs and spinules on the second dorsal and pelvic fin spines can lead to mortality. Therefore, it is considered essential to focus on managing the behavioral patterns and appropriate rearing density of red spotted grouper larvae from the emergence of barbs and spinules on the second dorsal and pelvic fin spines until they regress and metamorphosis is completed.